Peningkatan Kualitas Pembelajaran Berpikir Kritis melalui Model Think Pair Share (TPS) dalam Perspektif Pendidikan Islam di Sekolah Dasar - Marsela, Marsela; Siti Nurfauzia Azaini, Siti; Siti Yuliyati, Siti; Ridwan Firmansyah, Ridwan; Akmal Rizki Gunawan Hasibuan, Akmal (Universitas Majalengka, 2024)
The implementation of the Think Pair Share (TPS) learning model has been proven to significantly contribute to the development of students' critical thinking skills in Elementary School. Through this approach, students are not only encouraged to share ideas with their classmates but also prompted to think critically about the learning materials. Research findings indicate that students engaged in TPS experience improvements in analytical, evaluative, and synthesis abilities, which are crucial indicators of critical thinking. These positive implications demonstrate that the application of TPS is not only relevant in the classroom learning context but also holds great potential to enhance the effectiveness of the Campus Teaching Program in developing critical thinking skills among elementary school students.